Safer Healthcare 2016
DOI: 10.1007/978-3-319-25559-0_10
|View full text |Cite
|
Sign up to set email alerts
|

New Challenges for Patient Safety

Abstract: The developments described in the previous chapters are required because our present vision of safety is not adequate for the challenges we face. Our arguments for these developments rest on analyses of the nature of safety in healthcare as it is delivered today. However, as is well known, healthcare is changing rapidly and there are many new opportunities, pressures and challenges. We believe that these coming changes will have further implications for how safety is understood and practiced which will increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In high income countries, women with HDP are usually well managed with prompt, appropriate and effective interventions (Furuta, Sandall & Bick 2014). Despite this, some experience a life threatening event which may lead to psychological sequelae (Vincent 2006). This may impact adversely on mother-infant attachment and child development (Sharp et al 1995) and their overall experience.…”
Section: Introductionmentioning
confidence: 99%
“…In high income countries, women with HDP are usually well managed with prompt, appropriate and effective interventions (Furuta, Sandall & Bick 2014). Despite this, some experience a life threatening event which may lead to psychological sequelae (Vincent 2006). This may impact adversely on mother-infant attachment and child development (Sharp et al 1995) and their overall experience.…”
Section: Introductionmentioning
confidence: 99%
“…No health system is free of the occurrence of medical errors and harm to patients as studies over the world have shown that harm caused by healthcare affects all health systems. 14 It is estimated that around one in 10 patients admitted to hospital in the UK and other countries have a chance of being harmed. In Africa and the East Mediterranean, it is estimated that up to 18% of inpatient admissions were associated with adverse events.…”
Section: Unsafe Systemsmentioning
confidence: 99%
“…Patient safety has been defined as the ability of healthcare systems to minimize the occurrence and impact of unintended or unexpected harm to people during the provision of healthcare ( 1 ). It involves efforts to avoid, prevent, and reduce errors, adverse events, and injuries resulting from the provision of healthcare services ( 2 ). Adverse events, defined as “ unintended or unexpected incident which causes harm to a patient and may lead to temporary or permanent disability ( 3 ),” can happen in any healthcare setting.…”
Section: Introductionmentioning
confidence: 99%